Rheological evaluation of industrial tomato - Tóth, Anna Rita; Takácsné Hájos, Mária (Acta Agraria Debreceniensis, 2019)
Today, tomato has the second largest harvesting area globally, and the fourth largest in Hungary. The importance of industrial tomato is growing year by year, and one of the most important tasks is to satisfy the needs of the industry. To meet these needs, the producer has to find the proper genotype, which can achieve up to 100 t ha-1 crop yield. This quality has high importance to be researched. The experiment was carried out in the Botanical and Exhibition Garden of the University of Debrecen, with 3 examined genotypes. The planting date was 3 of May 2018. The harvesting was two-threaded. On 27 of July the physical parameters – fruit shape index (length/diameter), firmness (kg cm-2), water-soluble dry matter content (Brix%) and weight of the berries (g) – were evaluated. On 15 of August the rheological parameters were examined – the force needed to tear the skin – bioyield point (g) and flesh firmness (g). The fruit shape index was oval (between 1.19 and 1.24) for all the examined genotypes. The firmness was between 0.92 (UG1122713 F1) and 1.05(Prestomech F1) kg cm-2, which compliance the needs of the industry. The water-soluble dry matter content was suitable, with a value between 4.49 (Prestomech F1) and 4.65 (UG1122713 F1) Brix%. The weight of the berries was between 45.94 (UG989 F1) and 49.37 (Prestomech F1) g per piece. The bioyield point was between 76.00 (UG1122713 F1) and 85.16 (UG989 F1) g. The flesh firmness was between 33.68 (UG1122713 F1) and 42.81 (UG989 F1) g. Finally, we can conclude based on the obtained data that the UG989 F1 hybrid was the most proper for the applied cultivation conditions. This genotype can be recommended for the farmers even in extreme weather conditions.